The Role of Local Institutions in Establishing Collaborative Governance for Marine Ecotourism on Samalona Island - Andi Sulistiono; Agus Subianto; Sri Wahyuni; M Husni Thamrin (International Journal Labs, 2026)
The purpose of this research is to analyze the role of institutions in collaborative governance of marine ecotourism in the context of managing tourism in coastal areas and small islands. Research on the research of marine ecotourism governance on Samalona Island, Spermonde Islands, Makassar City. The results of the study show that marine ecotourism governance on Samalona Island is based on local communities that are implemented independently starting from the provision of homestays, diving equipment rentals, transportation services, culinary vendors and tour guides to addressing the problem of natural environmental damage. The policy of designating Samalona Island as a conservation area is not in line with the establishment of Samalona Island as a marine tourism destination in Makassar city, so that the achievement of the conservation area is difficult to achieve. Based on the research results, the researcher's recommendation is to strengthen the institutional design of marine ecotourism governance using a collaborative governance approach starting from strengthening the institutional actors of marine ecotourism governance with a marine perspective in a top-down manner with a strong commitment to building trust and implementing the concept of sustainable ecotourism that provides benefits for economic growth, improvement of socio-cultural life and preservation of the natural environment on Samalona Island. The conclusion of the research is that there is a need to strengthen the institutional design that applies marine ecotourism in collaborative governance between the Makassar City Government, the private sector and the local community.